2016
DOI: 10.1111/clr.12809
|View full text |Cite
|
Sign up to set email alerts
|

Osseoinductive elements around immediate implants for better osteointegration: a pilot study in foxhound dogs

Abstract: Within the limitations of this animal study, topical applications of 5% Melatonin or 10% vitamin D improved bone formation around implants placed immediately after extraction and helped to reduce CBL after 12 weeks osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…117 Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD. 124 Recently, the effect of topical application of vitamin D (10%) 125 and melatonin (5%) 126 solutions on the surface of immediate implants placed in dogs was evaluated. Both topical applications improved significantly new bone formation around implants and reduced crestal bone loss at 12 weeks following surgery, 126 standing out the positive correlation between vitamin D and early stages of osseointegration.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…117 Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD. 124 Recently, the effect of topical application of vitamin D (10%) 125 and melatonin (5%) 126 solutions on the surface of immediate implants placed in dogs was evaluated. Both topical applications improved significantly new bone formation around implants and reduced crestal bone loss at 12 weeks following surgery, 126 standing out the positive correlation between vitamin D and early stages of osseointegration.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
“…124 Recently, the effect of topical application of vitamin D (10%) 125 and melatonin (5%) 126 solutions on the surface of immediate implants placed in dogs was evaluated. Both topical applications improved significantly new bone formation around implants and reduced crestal bone loss at 12 weeks following surgery, 126 standing out the positive correlation between vitamin D and early stages of osseointegration. Therefore, these results may suggest that vitamin D has a protective effect on bone healing after implant insertion.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
“…Absence of melatonin or its inefficient production affects people who work on night shift, undergo changes in time zone, and suffer from insomnia 16 . In addition, melatonin interferes with bone healing in several ways: through modulation of inflammatory process, collagen fibril formation, osteoblast differentiation, and oxidative stress 6 , 9 , 10 , 15 , 26 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Both topical applications improved new bone formation around implants significantly and reduced crestal bone loss at 12 weeks following surgery, indicating the positive correlation between vitamin D and early stages of osseointegration. 18 Aydın et al 19 reported a significant increase in the amount of vitamin D in propolis groups and stated that the healing of the implanted bone was improved.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted on patients aged 18 Panoramic radiographs were taken with the same device (Veraviewpocs 2D, Morita, Japan) and with the same technical parameters (64-66 kVp; 6-9 mA; 10 s and voxel size 0.08 mm 3 ). Klemetti et al 7 defined MCI as C1, C2, C3 according to the visibility of the mandibular cortical bone.…”
Section: Methodsmentioning
confidence: 99%